The Strait of Malacca: Between Geo-economics Importance and Regional and International Security Challenges (قضايا سياسية, 2025)
The Strait of Malacca is one of the most important strategic sea lanes in the world, as it connects the Pacific and Indian Oceans, and is the main artery for the movement of trade and energy between East and West, and the importance of the Strait appears in geo-economic terms as it represents a corridor for about a quarter of the volume of world trade, more than (90,000) ships annually, and (30%) of global oil flows, making it a critical factor in the global economy, making it a decisive factor in the global economy.However, this importance is accompanied by increasing security challenges, including piracy, maritime terrorism, illegal fishing and environmental threats, as well as geopolitical competition between major powers and countries bordering the strait. The research concludes that maintaining the security of the strait requires increased regional and international cooperation and facing multiple challenges to ensure the sustainability of navigation in this vital corridor.